A kind of arsenic removal agent and preparation method thereof

By using polyethylene glycol and copper ion coating bonds and pyrine -based modified modified hydroxygenylite carriers, the existing arsenic of the existing arsenic is smaller and small. Achieve efficient and environmentally friendly arsenic removal effects.

CN118788294BActive Publication Date: 2025-01-28HUBEI JUNRAN NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411211901.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-28
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

The existing arsenic de-agents have problems such as small specific surface area, small pore volume, uneven dispersion of pore diameters, agglomeration of active ingredients, and high preparation costs, which affect their arsenic de-agent effect and environmental friendliness.

Method used

Polymiol and copper ions are used to form a fixing key, which combines modified hydroxytic hydroxylite modifiers modified by pyrine as a carrier to increase the load of the carrier to copper ions to prevent the gathering of copper ions and improve the performance of arsenic.

Benefits of technology

It significantly increases the arsenic capacity and arsenic rate of arsenic, extended the service life, reduced the preparation cost, and reduced environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of arsenic removal and purification, and specifically relates to a arsenic removal agent and a preparation method thereof. The arsenic removal agent provided by the present invention is prepared from a carbon hydroxyapatite carrier modified with polyethylene glycol, copper nitrate, and amidoxime. The present invention uses polyethylene glycol to form a coordination bond with copper ions, and uses modified hydroxyapatite modified with amidoxime as a carrier to increase the carrier's loading capacity for copper ions, prevent copper ions from agglomerating, and improve the arsenic removal performance of the arsenic removal agent; calcium nitrate, diammonium hydrogen phosphate, and sodium bicarbonate are used as raw materials, and carbonate is used to replace phosphate in hydroxyapatite to form carbon hydroxyapatite, reduce crystallinity, increase the pore size and specific surface area of ​​hydroxyapatite, and add starch during the granulation process, which effectively increases the porosity of the modified hydroxyapatite, improves the arsenic capacity of the modified hydroxyapatite, and improves the arsenic removal rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of arsenic removal and purification, and particularly relates to a arsenic removal agent and a preparation method thereof. Background Art

[0002] Petroleum contains many elements and their compounds that are harmful to the petroleum processing process, and arsenide is one of them. With the continuous progress of crude oil extraction, the arsenic content in oil products has been increasing year by year. Daqing oil and Xinjiang oil in my country are both high-arsenic crude oils, especially Daqing oil, which is considered to have the highest arsenic content in the world. Arsenides are widely present in various types of petroleum hydrocarbons, and products obtained from secondary processing of high-arsenic oil products, such as propylene, ethylene and other materials, also contain arsenides to varying degrees. Arsenides are easily deposited on the surface of pipelines, corroding pipelines, causing hidden dangers, and seriously affecting their processing, mainly manifested in the poisoning effect of arsenides on catalysts. Therefore, removing arsenides from petroleum has important practical value.

[0003] At present, the commonly used methods for removing arsenic from liquid hydrocarbons mainly include oxidative arsenic removal, catalytic hydrogenation arsenic removal and adsorption arsenic removal. Among them, adsorption arsenic removal has attracted widespread attention due to its simple process, easy handling and high efficiency. The adsorption arsenic removal agents used more in the prior art mainly include lead, manganese, copper, etc. Among them, the lead and manganese contained in the lead and manganese arsenic removal agents are heavy metals, which cause great pollution to the environment. The commonly used copper-based arsenic removal agent is a silicon-aluminum ball or activated carbon impregnated with 5%-10% copper sulfate. The catalyst activity of the copper sulfate silicon-aluminum ball adsorption method is low, the arsenic capacity is small, only 0.1%-0.3%, the operation cycle is also short, the consumption is large, and a large amount of waste catalysts is difficult to handle in time, which is easy to cause environmental pollution. In addition, the existing copper-based arsenic removal agents still have problems such as small specific surface area, small pore volume, and uneven dispersion of pore size, which affect their arsenic removal effect.

[0004] The Chinese patent application document with publication number CN105536689A discloses a supported arsenic removal agent and a preparation method thereof, comprising a carrier and an active component supported on the carrier; the carrier is a porous amorphous magnesium-aluminum spinel, and the active component is CuO and / or NiO. Since the carrier is a porous amorphous magnesium-aluminum spinel with good crystallinity, the material is internally bonded by strong Mg- and Al-O ionic bonds, which fundamentally and effectively improves the strength and hydration resistance of the material. However, the active ingredient copper oxide will agglomerate during the drying process, reducing the adsorption of arsenic.

[0005] The Chinese patent application document with publication number CN104549122A discloses a liquid hydrocarbon dearsenication catalyst, which adopts the active component Ni loaded on the γ-Al2O3 carrier, and is characterized in that the γ-Al2O3 carrier with a double pore size distribution is adopted, the pore radius of the small pores is 70-150, and the pore radius of the large pores is 2000-4000; it is impregnated twice with a soluble nickel salt solution, decomposed at a temperature of 250-350°C for 10-20 hours, and NiO grains less than 200 account for more than 95%; the catalyst is reduced in a mixed gas of H2 and N2, and then nitrogen and air are introduced at room temperature for passivation to obtain a pre-reduction catalyst; the pre-reduction catalyst is activated with hydrogen before use, and the activated catalyst performs a dearsenication reaction on arsenic-containing liquid hydrocarbon at a temperature of 80-250°C. The arsenic removal agent is a nickel-containing active component carried on a γ-Al2O3 carrier with a double pore distribution. The Ni content is 10-50%. It needs secondary impregnation and needs to be activated with hydrogen before use, and the preparation cost is relatively high. Summary of the invention

[0006] In order to solve the technical problems existing in the related art such as small specific surface area, small pore volume, uneven pore size dispersion, agglomeration of active ingredients, and high preparation cost, the purpose of the present invention is to provide a dearsenicizing agent and a preparation method thereof.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] A method for preparing a dearsenicating agent comprises the following steps: mixing polyethylene glycol and deionized water, adding copper nitrate and a carrier, ultrasonicating, vacuum drying after taking out, and calcining to prepare the dearsenicating agent;

[0009] The preparation method of the carrier is as follows: deionized water I and modified hydroxyapatite are placed in a three-necked flask, nitrogen is introduced, acrylonitrile and sodium carbonate are added, the mixture is stirred and heated once, methylenebisacrylamide and azobisisobutyronitrile are added, the mixture is kept warm for reaction, filtered, the filter residue is washed, and the mixture is put into the three-necked flask again, hydroxylamine hydrochloride, deionized water II, methanol and potassium carbonate are added, the mixture is stirred and heated for reaction twice, filtered, the filter residue is washed, and vacuum drying is performed to obtain the carrier.

[0010] In the present invention, polyethylene glycol is used to form a coordination bond with copper ions, so as to reduce the surface energy of copper ions, increase the stability of copper ions in a dearsenicating agent, and effectively prevent the agglomeration of copper ions. The modified hydroxyapatite modified with amidoxime groups is used as a carrier, so that not only the arsenic capacity of the dearsenicating agent can be increased, but also the amidoxime groups have a strong chelating effect on copper ions, so the loading amount of the carrier on copper ions can be increased, and the dearsenicating performance can be improved. At the same time, due to the steric hindrance effect of the amidoxime groups, the movement speed of copper ions is effectively reduced, the agglomeration of copper ions is prevented, and the dearsenicating performance of the dearsenicating agent is improved.

[0011] Furthermore, the preparation method of the modified hydroxyapatite in the carrier preparation method is as follows: (1) calcium nitrate and deionized water are mixed evenly, ammonia water is added, the temperature is raised by stirring, a mixed aqueous solution of diammonium phosphate and sodium bicarbonate is added dropwise, the reaction is kept warm, the mixture is cooled to room temperature, aged, filtered and washed until the pH value of the filtrate is 7.0, and the obtained solid is freeze-dried, sintered, and crushed to obtain porous carbon hydroxyapatite; (2) porous carbon hydroxyapatite, zinc borate and starch are placed in a mixing granulator, and a carboxymethyl cellulose solution is sprayed to obtain spherical particles; the spherical particles are dried and then roasted to obtain modified hydroxyapatite.

[0012] In the present invention, calcium nitrate, diammonium hydrogen phosphate and sodium bicarbonate are used as raw materials to prepare porous carbon hydroxyapatite. The addition of carbonate ions reduces the crystallinity of the prepared hydroxyapatite, improves dispersibility, and makes the particles finer, which is more conducive to the adsorption of copper ions and arsenic ions, and can also increase the pore size and specific surface area of ​​the hydroxyapatite. Starch is added during the granulation process to effectively increase the porosity of the modified hydroxyapatite. The increase in the pore size and specific surface area of ​​the carrier can load more copper ions, which is the key to improving the arsenic removal performance and extending the service life of the arsenic removal agent.

[0013] Furthermore, in the step (1) of the preparation method of modified hydroxyapatite, the mixing mass ratio of diammonium hydrogen phosphate and sodium bicarbonate is 50-53:1, and the mass percentage of the mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate is 7-9%; the dripping time of the mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate is controlled to be 1-1.2h.

[0014] In the present invention, the content of carbonate in the modified hydroxyapatite is controlled by controlling the mixing mass ratio of diammonium hydrogen phosphate and sodium bicarbonate, thereby controlling the grain size and morphology of the modified hydroxyapatite, which is a key influencing factor for adjusting the arsenic removal performance of the arsenic removal agent. Studies have found that when the mixing mass ratio of diammonium hydrogen phosphate and sodium bicarbonate is within the range of the present invention, the specific surface area and surface activity of the prepared modified hydroxyapatite are optimal, and it has good biocompatibility and adsorption performance for metal ions.

[0015] Furthermore, the weight proportions of the components in step (1) of the preparation method of modified hydroxyapatite are: 30-35 parts of calcium nitrate, 50-55 parts of deionized water, 10-15 parts of ammonia water, and 115-120 parts of a mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate; the stirring and heating temperature is 85-90°C; the insulation reaction time is 4.7-5.2h; the aging time is 22-24h; the sintering temperature is 560-630°C, and the sintering time is 5.7-6.2h.

[0016] Furthermore, the weight proportions of the components in step (2) of the preparation method of the modified hydroxyapatite are: 88-93 parts of porous carbon hydroxyapatite, 5-10 parts of zinc borate, 5-10 parts of starch, and 50-60 parts of carboxymethyl cellulose solution; the preparation method of the carboxymethyl cellulose solution is: take 3-5 parts of carboxymethyl cellulose and 200 parts of deionized water, mix them evenly, stir and boil for 1.5-1.7 hours, and cool to obtain a carboxymethyl cellulose solution.

[0017] Furthermore, in the preparation method of modified hydroxyapatite, the drying temperature in step (2) is 90-100°C, and the drying time is 13-15h; the calcination is specifically: heating to 400°C at a rate of 2-5°C / min, keeping warm for 2-4h, then heating to 700°C at the same rate, and keeping warm for 4-4.5h.

[0018] Furthermore, the weight proportions of the components in the preparation method of the carrier are: 140-150 parts of deionized water I, 12-14 parts of modified hydroxyapatite, 1-5 parts of acrylonitrile, 0.2-1 parts of sodium carbonate, 0.1-0.3 parts of methylenebisacrylamide, 0.3-0.5 parts of azobisisobutyronitrile, 8-12 parts of hydroxylamine hydrochloride, 45-55 parts of deionized water II, 45-52 parts of methanol, and 6-8 parts of potassium carbonate.

[0019] Furthermore, in the preparation method of the carrier, the temperature of the first stirring and heating is 70-80°C, and the insulation reaction time is 6.8-7.3h; the temperature of the second stirring and heating is 60-70°C, and the reaction time is 3.5-4h; the temperature of vacuum drying is 50-55°C, and the vacuum drying time is 11-13h.

[0020] Furthermore, the weight proportions of the components in the preparation method of the arsenic removal agent are: 0.01-1 parts of polyethylene glycol, 95-100 parts of deionized water, 5-10 parts of copper nitrate, and 12-15 parts of a carrier; the molecular weight of the polyethylene glycol is 400; the frequency of the ultrasound is 200-300kHz, and the ultrasound time is 3.5-4h; the vacuum drying temperature is 100-120°C, and the vacuum drying time is 9-11h; the calcination temperature is 500-600°C, and the calcination time is 3.8-4.2h.

[0021] The present invention also provides a dearsenicating agent prepared by the preparation method of the dearsenicating agent.

[0022] Compared with the prior art, the arsenic removal agent and preparation method provided by the present invention have the following technical advantages:

[0023] (1) The present invention uses polyethylene glycol to form a coordination bond with copper ions to increase the stability of copper ions in the arsenic removal agent, and uses modified hydroxyapatite modified with amidoxime groups as a carrier to increase the carrier's loading capacity for copper ions, prevent copper ions from agglomerating, and improve the arsenic removal performance of the arsenic removal agent;

[0024] (2) In the present invention, calcium nitrate, diammonium hydrogen phosphate and sodium bicarbonate are used as raw materials, and carbonate is used to replace phosphate in hydroxyapatite to form carbon hydroxyapatite, thereby reducing the crystallinity and increasing the pore size and specific surface area of ​​hydroxyapatite. Starch is added during the granulation process to effectively increase the porosity of the modified hydroxyapatite, improve the arsenic capacity of the modified hydroxyapatite, and improve the arsenic removal rate;

[0025] (3) The preparation method of the arsenic removal agent provided by the present invention is simple, the conditions are controllable, and the arsenic removal effect of the prepared arsenic removal agent is good, which is of great significance for reducing arsenic emissions. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. Those skilled in the art can make various modifications based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention.

[0027] Example 1

[0028] A method for preparing a dearsenicating agent comprises the following steps: mixing 0.01 parts of polyethylene glycol with a molecular weight of 400 with 100 parts of deionized water, adding 5 parts of copper nitrate and 12 parts of a carrier, ultrasonicating at a frequency of 200 kHz for 4 hours, vacuum drying at 100° C. for 11 hours, and calcining at 500° C. for 4.2 hours to obtain the dearsenicating agent.

[0029] The preparation method of the carrier is as follows: 140 parts of deionized water and 14 parts of modified hydroxyapatite are placed in a three-necked flask, nitrogen is introduced, 5 parts of acrylonitrile and 1 part of sodium carbonate are added, the mixture is stirred and heated to 70°C, 0.3 parts of methylenebisacrylamide and 0.5 parts of azobisisobutyronitrile are added, the mixture is kept warm for reaction for 6.8 hours, filtered, the filter residue is washed once with isopropanol and then washed three times with deionized water, the mixture is put into the three-necked flask again, 8 parts of hydroxylamine hydrochloride, 55 parts of deionized water, 45 parts of methanol and 6 parts of potassium carbonate are added, the mixture is stirred again and heated to 60°C for reaction for 4 hours, filtered, washed three times with deionized water, and placed in a vacuum oven for vacuum drying at 50°C for 13 hours to obtain the carrier.

[0030] The preparation method of the modified hydroxyapatite is as follows: (1) 30 parts of calcium nitrate and 55 parts of deionized water are mixed evenly, 10 parts of ammonia water are added, the mixture is stirred and heated to 85°C, 115 parts of a mixed aqueous solution of 7% by mass of diammonium hydrogen phosphate and sodium bicarbonate are added dropwise, the mixed mass ratio of diammonium hydrogen phosphate and sodium bicarbonate is 50:1, the addition time of the mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate is controlled to be 1 hour, the mixture is kept warm for 4.7 hours, cooled to room temperature, aged for 22 hours, and filtered and washed until the pH value of the filtrate is 7.0 , freeze-dry the obtained solid, sinter at 560°C for 6.2h, and crush to obtain porous carbon hydroxyapatite; (2) place 88 parts of porous carbon hydroxyapatite, 5 parts of zinc borate and 5 parts of starch in a mixing granulator, spray 50 parts of carboxymethyl cellulose solution to obtain spherical particles; dry the spherical particles at 90°C for 15h, heat to 400°C at a rate of 2°C / min, keep warm and roast for 2h, then heat to 700°C at the same rate, keep warm and roast for 4h, and obtain spherical modified hydroxyapatite with a diameter of 3mm. The preparation method of the carboxymethyl cellulose solution is as follows: take 3 parts of carboxymethyl cellulose and 200 parts of deionized water, mix them evenly, stir and boil for 1.5h, cool, and obtain a carboxymethyl cellulose solution.

[0031] Example 2

[0032] A method for preparing a dearsenicating agent comprises the following steps: mixing 1 part of polyethylene glycol with a molecular weight of 400 and 95 parts of deionized water, adding 10 parts of copper nitrate and 15 parts of a carrier, ultrasonicating for 3.5 hours at a frequency of 300 kHz, vacuum drying at 120° C. for 9 hours, and calcining at 600° C. for 3.8 hours to obtain the dearsenicating agent.

[0033] The preparation method of the carrier is as follows: 150 parts of deionized water and 12 parts of modified hydroxyapatite are placed in a three-necked flask, nitrogen is introduced, 1 part of acrylonitrile and 0.2 parts of sodium carbonate are added, the mixture is stirred and heated to 80°C, 0.1 parts of methylenebisacrylamide and 0.3 parts of azobisisobutyronitrile are added, the mixture is kept warm for reaction for 7.3 hours, filtered, the filter residue is washed once with isopropanol and then washed three times with deionized water, the mixture is put into the three-necked flask again, 12 parts of hydroxylamine hydrochloride, 45 parts of deionized water, 52 parts of methanol and 8 parts of potassium carbonate are added, the mixture is stirred again and heated to 70°C for reaction for 3.5 hours, filtered, washed three times with deionized water, and placed in a vacuum oven for vacuum drying at 55°C for 11 hours to obtain the carrier.

[0034] The preparation method of the modified hydroxyapatite is as follows: (1) 35 parts of calcium nitrate and 50 parts of deionized water are mixed evenly, 15 parts of ammonia water are added, the mixture is stirred and heated to 90°C, 120 parts of a mixed aqueous solution of 9% by mass of diammonium hydrogen phosphate and sodium bicarbonate are added dropwise, the mixed mass ratio of diammonium hydrogen phosphate and sodium bicarbonate is 53:1, the addition time of the mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate is controlled to be 1.2 hours, the mixture is kept warm for 5.2 hours, cooled to room temperature, aged for 24 hours, filtered and washed until the pH value of the filtrate is 7.0, and the mixture is washed with suction. The obtained solid was freeze-dried, sintered at 630°C for 5.7h, and crushed to obtain porous carbon hydroxyapatite; (2) 93 parts of porous carbon hydroxyapatite, 10 parts of zinc borate and 10 parts of starch were placed in a mixing granulator, and 60 parts of carboxymethyl cellulose solution were sprayed to obtain spherical particles; the spherical particles were dried at 100°C for 15h, heated to 400°C at a rate of 5°C / min, kept warm and roasted for 4h, and then heated to 700°C at the same rate, kept warm and roasted for 4.5h to obtain spherical modified hydroxyapatite with a diameter of 3mm. The preparation method of the carboxymethyl cellulose solution is as follows: 5 parts of carboxymethyl cellulose and 200 parts of deionized water are mixed evenly, stirred and boiled for 1.7h, and cooled to obtain a carboxymethyl cellulose solution.

[0035] Example 3

[0036] A method for preparing a dearsenicating agent comprises the following steps: mixing 0.5 parts of polyethylene glycol with a molecular weight of 400 and 97 parts of deionized water, adding 8 parts of copper nitrate and 13 parts of a carrier, ultrasonicating for 3.8 hours at a frequency of 250 kHz, vacuum drying at 110° C. for 10 hours, and calcining at 580° C. for 4.0 hours to obtain the dearsenicating agent.

[0037] The preparation method of the carrier is as follows: 145 parts of deionized water and 13 parts of modified hydroxyapatite are placed in a three-necked flask, nitrogen is introduced, 3 parts of acrylonitrile and 0.7 parts of sodium carbonate are added, the mixture is stirred and heated to 75°C, 0.2 parts of methylenebisacrylamide and 0.4 parts of azobisisobutyronitrile are added, the mixture is kept warm for reaction for 7.0 hours, filtered, the filter residue is washed once with isopropanol and then washed three times with deionized water, the mixture is put into the three-necked flask again, 10 parts of hydroxylamine hydrochloride, 50 parts of deionized water, 49 parts of methanol and 7 parts of potassium carbonate are added, the mixture is stirred again and heated to 65°C for reaction for 3.8 hours, filtered, washed three times with deionized water, and placed in a vacuum oven for vacuum drying at 53°C for 12 hours to obtain the carrier.

[0038] The preparation method of the modified hydroxyapatite is as follows: (1) 33 parts of calcium nitrate and 54 parts of deionized water are mixed evenly, 13 parts of ammonia water are added, the mixture is stirred and heated to 88°C, 118 parts of a mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate with a mass percentage of 8% are added dropwise, the mixed mass ratio of diammonium hydrogen phosphate and sodium bicarbonate is 52:1, the dropping time of the mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate is controlled to be 1.1 hours, the mixture is kept warm for 5.0 hours, cooled to room temperature, aged for 23 hours, and filtered and washed until the pH value of the filtrate is 7.0 , freeze-dry the obtained solid, sinter at 600°C for 6.0h, and crush to obtain porous carbon hydroxyapatite; (2) place 90 parts of porous carbon hydroxyapatite, 8 parts of zinc borate and 8 parts of starch in a mixing granulator, spray 56 parts of carboxymethyl cellulose solution to obtain spherical particles; dry the spherical particles at 95°C for 14h, heat to 400°C at a rate of 3°C / min, keep warm and roast for 3h, then heat to 700°C at the same rate, keep warm and roast for 4.2h, and obtain spherical modified hydroxyapatite with a diameter of 3mm. The preparation method of the carboxymethyl cellulose solution is as follows: take 4 parts of carboxymethyl cellulose and 200 parts of deionized water, mix them evenly, stir and boil for 1.6h, cool, and obtain a carboxymethyl cellulose solution.

[0039] Comparative Example 1

[0040] The preparation method of the arsenic removal agent in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that an equal amount of biuret is used instead of polyethylene glycol in this comparative example.

[0041] Comparative Example 2

[0042] The preparation method of the arsenic removal agent in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that an equal amount of diammonium hydrogen phosphate is used instead of sodium bicarbonate in the preparation method of the modified hydroxyapatite in this comparative example.

[0043] Comparative Example 3

[0044] The preparation method of the arsenic removal agent in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that an equal amount of deionized water is used instead of hydroxylamine hydrochloride in the preparation method of the carrier in this comparative example.

[0045] Comparative Example 4

[0046] The preparation method of the arsenic removal agent in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that an equal amount of carboxymethyl cellulose solution is used instead of starch in the preparation method of the modified hydroxyapatite in this comparative example.

[0047] Comparative Example 5

[0048] The preparation method of the arsenic removal agent in this comparative example is similar to that in Example 3. The difference between this comparative example and Example 3 is that the mixing mass ratio of diammonium hydrogen phosphate and sodium bicarbonate in step (1) of the preparation method of modified hydroxyapatite in this comparative example is 3:7.

[0049] Test example

[0050] The arsenic removal agents prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were used to remove arsenic from arsenic-containing gasoline. 5 L of arsenic-containing gasoline was taken and placed in a reactor. The amount of the arsenic removal agent met the height-diameter ratio (4-5). The evaluation was performed in a bottom-in and top-out manner. The outlet was tested using a trace arsenic meter. The arsenic content was calculated when the outlet gas concentration reached 10 ppm. The arsenic removal temperature was room temperature and the air velocity was 6 h -1 , the test results are shown in Table 1.

[0051] Table 1 Arsenic removal performance test results

[0052]

[0053] As can be seen from Table 1, the arsenic removal accuracy of the arsenic removal agent provided by the present invention is less than 1.0, the arsenic removal rate is greater than 90%, the arsenic capacity is greater than 90%, and the arsenic removal effect is stable within 400 hours, and it has a good arsenic removal effect. Among them, the arsenic removal agent prepared in Example 3 has the best performance and is the best embodiment of the present invention.

[0054] Compared with Example 3, in Comparative Example 1, an equal amount of biuret was used instead of polyethylene glycol, but the arsenic removal rate and arsenic capacity of the obtained arsenic removal agent decreased, which indicates that not all substances that can form coordination bonds with copper ions can play the role of polyethylene glycol; in Comparative Example 2, an equal amount of diammonium hydrogen phosphate was used instead of sodium bicarbonate, but the arsenic removal rate and arsenic capacity of the obtained arsenic removal agent were significantly reduced, which indicates that the addition of titanate can increase the pore size and specific surface area of ​​hydroxyapatite, and effectively improve the arsenic capacity and arsenic removal rate; in the preparation method of the carrier in Comparative Example 3, an equal amount of deionized water was used instead of hydroxylamine hydrochloride, but the arsenic removal rate of the obtained arsenic removal agent was significantly reduced, and the arsenic capacity was slightly reduced, which indicates that the addition of titanate can increase the pore size and specific surface area of ​​hydroxyapatite, and effectively improve the arsenic capacity and arsenic removal rate. The amine oxime group has a strong chelating effect on copper ions. At the same time, due to its steric hindrance effect, it can prevent copper ions from agglomerating and improve the arsenic removal performance. In the preparation method of modified hydroxyapatite in comparative example 4, an equal amount of carboxymethyl cellulose solution is used instead of starch, but the arsenic removal rate and arsenic capacity of the obtained arsenic removal agent are significantly reduced, which indicates that in the preparation process of modified hydroxyapatite, adding starch can effectively increase the porosity of the modified hydroxyapatite and increase the specific surface area. In comparative example 5, the mixing mass ratio of diammonium hydrogen phosphate and sodium bicarbonate is changed, but the arsenic removal rate and arsenic capacity of the obtained arsenic removal agent are reduced, which indicates that the mixing mass ratio of diammonium hydrogen phosphate and sodium bicarbonate in the present invention has been optimized.

[0055] The above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any person skilled in the art shall not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, any modification, equivalent substitution and improvement made by those skilled in the art under the technical concept of the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a dearsenicating agent, characterized in that: Specifically, polyethylene glycol and deionized water are mixed, copper nitrate and a carrier are added, ultrasonic treatment is performed, vacuum drying is performed after removal, and calcination is performed to obtain a dearsenicizing agent; the weight proportions of the components are: 0.01-1 parts of polyethylene glycol, 95-100 parts of deionized water, 5-10 parts of copper nitrate, and 12-15 parts of the carrier; The preparation method of the carrier is as follows: deionized water I and modified hydroxyapatite are placed in a three-necked flask, nitrogen is introduced, acrylonitrile and sodium carbonate are added, stirring and heating once, methylenebisacrylamide and azobisisobutyronitrile are added, heat-retaining reaction is carried out, filtering is performed, the filter residue is washed and then put into the three-necked flask again, hydroxylamine hydrochloride, deionized water II, methanol and potassium carbonate are added, stirring and heating reaction is carried out for a second time, filtering is performed, the filter residue is washed, and vacuum drying is performed to obtain the carrier; the weight proportions of the components are as follows: deionized water I 140-150 parts, modified hydroxyapatite 12-14 parts, acrylonitrile 1-5 parts, sodium carbonate 0.2-1 parts, methylenebisacrylamide 0.1-0.3 parts, azobisisobutyronitrile 0.3-0.5 parts, hydroxylamine hydrochloride 8-12 parts, deionized water II 45-55 parts, methanol 45-52 parts, and potassium carbonate 6-8 parts; The preparation method of the modified hydroxyapatite is as follows: (1) mixing calcium nitrate and deionized water uniformly, adding ammonia water, stirring and heating, dripping a mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate with a mass percentage of 7-9%, the mixed mass ratio of diammonium hydrogen phosphate and sodium bicarbonate is 50-53:1, controlling the dripping time of the mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate to be 1-1.2 hours, keeping the temperature for reaction, cooling to room temperature, aging, filtering and washing until the pH value of the filtrate is 7.0, freeze-drying the obtained solid, sintering, and crushing to obtain porous carbon hydroxyapatite; (2) Apatite, zinc borate and starch are placed in a mixing granulator, and a carboxymethyl cellulose solution is sprayed into the spherical particles to obtain spherical particles; the spherical particles are dried and then roasted to obtain modified hydroxyapatite; the weight proportions of the components in step (1) are: 30-35 parts of calcium nitrate, 50-55 parts of deionized water, 10-15 parts of ammonia water, and 115-120 parts of a mixed aqueous solution of diammonium hydrogen phosphate and sodium bicarbonate; the weight proportions of the components in step (2) are: 88-93 parts of porous carbon hydroxyapatite, 5-10 parts of zinc borate, 5-10 parts of starch, and 50-60 parts of carboxymethyl cellulose solution.

2. The method for preparing the arsenic removal agent according to claim 1, characterized in that: In the preparation method of modified hydroxyapatite, the stirring and heating temperature in step (1) is 85-90°C; the heat preservation reaction time is 4.7-5.2h; the aging time is 22-24h; the sintering temperature is 560-630°C, and the sintering time is 5.7-6.2h.

3. The method for preparing the arsenic removal agent according to claim 1, characterized in that: The preparation method of the carboxymethyl cellulose solution in step (2) of the preparation method of modified hydroxyapatite is: take 3-5 parts of carboxymethyl cellulose and 200 parts of deionized water, mix them evenly, stir and boil for 1.5-1.7 hours, and cool to obtain a carboxymethyl cellulose solution.

4. The method for preparing the arsenic removal agent according to claim 1, characterized in that: In step (2) of the preparation method of modified hydroxyapatite, the drying temperature is 90-100°C and the drying time is 13-15h; the calcination is specifically as follows: heating to 400°C at a rate of 2-5°C / min, keeping the temperature for 2-4h, then heating to 700°C at the same rate and keeping the temperature for 4-4.5h.

5. The method for preparing the arsenic removal agent according to claim 1, characterized in that: In the preparation method of the carrier, the temperature of the first stirring and heating is 70-80°C, and the insulation reaction time is 6.8-7.3h; the temperature of the second stirring and heating is 60-70°C, and the reaction time is 3.5-4h; the temperature of the vacuum drying is 50-55°C, and the vacuum drying time is 11-13h.

6. The method for preparing the arsenic removal agent according to claim 1, characterized in that: The molecular weight of the polyethylene glycol is 400; the frequency of the ultrasound is 200-300kHz, and the ultrasound time is 3.5-4h; the vacuum drying temperature is 100-120°C, and the vacuum drying time is 9-11h; the calcination temperature is 500-600°C, and the calcination time is 3.8-4.2h.

7. The arsenic removal agent prepared according to the preparation method of the arsenic removal agent according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Room-temperature desulfurization and dearsenification agent and preparation method thereof

    CN104549122A

  • Loaded type dearsenicating agent and preparation method thereof

    CN105536689A

  • Modified walnut-shell adsorbent containing double amidoxime groups and preparation method thereof

    CN103752279A

  • Preparation method of carbonate hydroxylapatite-carbon aerosol composite material

    CN104741067A